2005
DOI: 10.1016/j.pain.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and motor effects of experimental muscle pain in patients with lateral epicondylalgia and controls with delayed onset muscle soreness

Abstract: This study compares the effect of experimental muscle pain on deep tissue sensitivity and force attenuation in the wrist extensors of patients with lateral epicondylalgia (n=20), and healthy controls (n=20) with experimentally induced sensori-motor characteristics simulating lateral epicondylalgia. Delayed onset muscle soreness (DOMS) in wrist extensors of healthy controls was induced by eccentric exercise in one arm 24h prior to injection (Day 0). Saline-induced pain intensity (visual analogue scale, VAS), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 56 publications
12
98
0
8
Order By: Relevance
“…Previous studies demonstrated that females have less-efficient pain habituation, greater susceptibility for developing temporal summation of mechanically evoked pain, 48 and less-efficient diffuse noxious inhibitory controls than males. 13,51,54 Therefore, we do not know if our results would be similar in males. Studies with greater sample sizes are needed to permit a more generalized interpretation of these results.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies demonstrated that females have less-efficient pain habituation, greater susceptibility for developing temporal summation of mechanically evoked pain, 48 and less-efficient diffuse noxious inhibitory controls than males. 13,51,54 Therefore, we do not know if our results would be similar in males. Studies with greater sample sizes are needed to permit a more generalized interpretation of these results.…”
Section: Discussionmentioning
confidence: 75%
“…no prior injection of NGF) into ECRB (Slater et al 2005) did not affect PPT at the injection site, which suggests that injection of hypertonic saline into ECRB does not affect PPT at the elbow, whether pre-sensitized with NGF or not.…”
Section: Effects Of Superimposed Injection Of Hypertonic Salinementioning
confidence: 91%
“…First, NGF injection induced pain that was evoked during movement for approximately one week after a single injection (Andersen et al 2008; Study 4) and two weeks after multiple injections (Hayashi et al 2013). In contrast, pain from hypertonic saline injection lasted for up to 10 minutes and DOMS-related pain was sustained for 2-3 days after exercise (Slater et al 2005). Second, pain that is induced by injection of NGF was evoked by contraction and stretch of ECRB.…”
Section: Ngf As a Model Of Sustained Elbow Painmentioning
confidence: 99%
“…Esta teoría está basada en la suposición de que la abertura de estas conexiones se produce por la aferentación nociceptiva desde los músculos esqueléticos y de que el dolor referido a los miotomas fuera de la lesión ocurre por la propagación de la sensibilización central a los segmentos medulares adyacentes. Sin embargo, los estudios del DMR inducido experimentalmente por Laursen y colaboradores (15)(16)(17)(18)(19) han mostrado que la producción del dolor muscular referido es dependiente del dolor muscular local y muestra una correlación con este.…”
Section: Introductionunclassified
“…Otros estímulos llegan a la médula espinal de los puntos gatillo distales y áreas disfuncionales adicionales (E y F). Los hallazgos de que los PGM causan el DR ponen en seria duda la validez interna del concepto (19). En casos crónicos el DMR se explica por el ciclo de retroalimentación mantenido por los centros cerebrales superiores que reciben impulsos originados en los PGM.…”
Section: Introductionunclassified